Well-informed and willing, but breastfeeding does not work: a qualitative study on perceived support from health professionals among German mothers with breastfeeding problems - Spannhake, Mariz; Jansen, Charlotte Elisabeth; Görig, Tatiana; Diehl, Katharina (Healthcare, 2022)
Although exclusive breastfeeding is recommended for the first six months of life, a large number of women worldwide do not practice it successfully. Our study aimed to investigate the perceived support from health professionals for women who experienced difficulties in breastfeeding. Furthermore, we examined women’s knowledge about breastfeeding and motivation to breastfeed. We conducted a qualitative exploratory study (June to October 2019) among 15 women who had experienced breastfeeding problems in Germany. Semi-structured interviews were audiotaped, transcribed verbatim, and analyzed using qualitative content analysis following Mayring’s approach. Prior to giving birth, the women’s motivation to breastfeed and theoretical knowledge were high, and breastfeeding problems were not anticipated. Difficulties in breastfeeding after giving birth created a highly demanding situation for the mothers. Health professionals were either perceived as very supportive, for example, by providing helpful technical advice or being emotional assistance, or they could be perceived as nonhelpful, thereby worsening the situation, for example, by pressuring the women to breastfeed or making improper remarks. Adequate support for young mothers in childbed consists of the provision of useful and realistic information concerning breastfeeding and a sensitive treatment when breastfeeding problems occur. Paying attention to this specific group of women who are experiencing difficulties in breastfeeding may improve maternal and child well-being and potentially enable breastfeeding.
Gesehen am 06.02.2024